Comparison of Concrete Properties determined by Destructive and Non-Destructive Tests - Shankar, Siddharth; Joshi, Hikmat Raj (Journal of the Institute of Engineering, 2014)
Federation of Contractor Associations of Nepal (FCAN) has asked the government to amend the law so that bidders quoting the average price would be awarded the contract. The competitive bidding process for awarding construction contracts in Nepal is based on the low bid method. According to this method, the construction firm submitting the lowest bid receives the right to the construction contract. Promoting competition amongst contractors and maintaining transparency are the clear benefits but delays in meeting the contract duration, increment of the final project cost, tendency to compromise quality, and adversarial relationship among contracting parties are the major drawbacks.As alternative of low bid method, some countries are using Average bid method.In this method, contract is awarded to the contractor whose price is closest to the average of all bids submitted. It is assumed that with a fair price they would conform to quality requirements of the project, would complete on time, and would not have adversarial relationships with the consultant of the employer. Awarding tenders to the lowest bidders is the major reason behind lingering construction projects and failure in meeting its standards in Nepal. To avoid such problems, Average bid Award system may be practiced by public agencies for procurement of works in Nepal. DOI: http://dx.doi.org/10.3126/jie.v10i1.10889 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 130–139